Chemical modulation of bioactive compounds via oligopeptide or amino acid conjugation. Issue 6 (November 2013) - Kwak, Seon‐Yeong; Yang, Jin‐Kyoung; Kim, Jong‐Ho; Lee, Yoon‐Sik; Gierasch, Lila; Lynn, David; Schneider, Joel
ABSTRACT Conjugation of an oligopeptide or an amino acid to bioactive compounds is one of the simplest chemical modifications to modulate the biological functions of the compounds. Recently, numerous methods have been proposed for the modification of their properties, including the alteration of their chemical and physical properties, and of their original bioactivities. We review the current knowledge of the adaptability of oligopeptide or amino acid conjugation for modulating the biological activities of biomolecules. © 2013 Wiley Periodicals, Inc. Biopolymers (Pept Sci) 100: 584–591, 2013.